A (Simple) Experimental Demonstration that Cultural Evolution is not Replicative, but Reconstructive — and an Explanation of Why this Difference Matters - Scott-Phillips, Thomas C. (Journal of cognition and culture, 2017)
Two complementary approaches to a naturalistic theory of culture are, on the one hand, mainstream cultural evolution research, and, on the other, work done under the banners of cultural attraction and the epidemiology of representations. There is much agreement between these two schools of thought, including in particular a commitment to population thinking. Both schools also acknowledge that the propagation of culture is not simply a matter of replication, but rather one of reconstruction. However, the two schools of thought differ on the relative importance of this point. The cultural attraction school believes it to be fundamental to genuinely causal explanations of culture. In contrast, most mainstream cultural evolution thinking abstracts away from it. In this paper I make flesh a simple thought experiment (first proposed by Dan Sperber) that directly contrasts the effects that replication and reconstruction have on cultural items. Results demonstrate, in a simple and graphic way, that (i) normal cultural propagation is not replicative, but reconstructive, and (ii) that these two different modes of propagation afford two qualitatively different explanations of stability. If propagation is replicative, as it is in biology, then stability arises from the fidelity of that replication, and hence an explanation of stability comes from an explanation of how and why this high-fidelity is achieved. If, on the other hand, propagation is reconstructive (as it is in culture), then stability arises from the fact that a subclass of cultural types are easily re-producible, while others are not, and hence an explanation of stability comes from a description of what types are easily re-producible, and an explanation of why they are. I discuss two implications of this result for research at the intersection of evolution, cognition, and culture.